Effects of soil type and irrigation on yield and quality of 'Kirmizi' pistachio cultivar - Ak B.E.; Agackesen N. (XIII GREMPA Meeting on Almonds and Pistachios, 2005)
This work was conducted for the determination of yield and quality of 'Kirmizi' pistachio cv. grown in: (i) arid and poor soils; and (ii) fertile soils. Both soils receive treatments with and without irrigation. The experiments were designed with 4 treatments and 3 replicates. There were 5 trees in each replicate and each tree was treated as one replicate. The whole experiment consisted of 60 trees. The trees were in their 'on' year. They were all 30 years old. The harvested nuts were weighed fresh and dried (sun dried for 5 days). Pomological and physical characteristics of the nuts were determined. According to the results obtained, yield, nut size, shelling and splitting percentages increased with irrigation in both poor and fertile soils.
13. Meeting of the Mediterranean Research Group for Almond and Pistachio, 2003/06/01-05, Mirandela (Portugal)